Mycotic aortic aneurysm secondary to spondylodiscitis: A case report and review - Hicham Benramdane; Hamid Ziani; Siham Nasri; Imane Kamaoui; Imane Skiker (Radiology Case Reports)
Mycotic aneurysms are a rare but potentially life-threatening complication of infections, particularly those involving the spine. Spondylodiscitis, a bacterial or fungal infection of the intervertebral disc, is a known risk factor for the development of mycotic aneurysms. Early diagnosis and prompt treatment are crucial for improving patient outcomes. We report the case of a 79-year-old patient with a history of diabetes admitted for chronic back pain refractory to medical treatment. A cervico-thoraco-abdomino-pelvic CT scan showed infectious spondylodiscitis at the lumbar level complicated by a mycotic aneurysm of the infrarenal abdominal aorta. This case highlights the diagnostic challenges associated with mycotic aneurysms, particularly when they arise from a contiguous infectious focus. Imaging modalities, such as computed tomography (CT) and magnetic resonance imaging (MRI), play a pivotal role in identifying these aneurysms and assessing their extent.The patient underwent surgical management of the spondylodiscitis and the mycotic aneurysm. A stent was placed to reinforce the weakened aortic wall and prevent rupture. Postoperative management included long-term antibiotic therapy to eradicate the infection. The patient experienced a favorable outcome, with resolution of symptoms and improved quality of life.